Experiences of inter- and transdisciplinary research – a trajectory of knowledge integration within a large research consortium - Schönenberg, Regine; Boy, Jens; Hartberger, Korbinian; Schumann, Charlotte; Guggenberger, Georg; Siebold, Matthias; Lakes, Tobia; Lamparter, Gabriele; Schindewolf, Marcus; Schaldach, Rüdiger; Nendel, Claas; Hohnwald, Stefan; et al. (ERDKUNDE, 2017)
Although inter- and transdisciplinary research has found its way to the forefront of calls, funding and publications, interdisciplinary projects often start from scratch constructing their research environment. In this article we will point to the enormous potential, the learnings, as well as some of the difficulties and pitfalls frequently encountered in large interdisciplinary project consortia. With this in mind, we aim to transparently document and reflect upon our research process, reminding the readers that the authors are not academic specialists in the field of inter- and transdisciplinarity nor in the sociology of knowledge. To explain our motivation, we want to share valuable experiences and point to some learnings, especially regarding the interdependencies between inter- and transdisciplinarity. After a brief historical retrospective of the expectations towards science, the article describes the trajectory of knowledge production and integration of a rather large research consortium attempting to overcome typical communicative and conceptual hurdles while negotiating the strict preconceptions of the respective disciplines. During the process of knowledge integration, scientific recognition and time budgets remain the crucial challenges. Besides joint field research, the construction of four storylines and the continuous integration of data into the various and increasingly interlinked models that ultimately culminate in our future scenarios led to constant communication and disputes among the subprojects involved. During the course of the project, it became obvious that a new generation of young scientists is developing: scientists working in interdisciplinary and transdisciplinary thought communities with a grasp of both fundamental science and transdisciplinary practice, combined with the soft skills necessary to reconcile both worlds.